Content Analysis of English Learning Material for SMK/MAK XI 2013 Curriculum Published by Bumi Aksara - Anggie Anggie; Suparmi Suparmi; Rahma Dania (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
The reseach queations in this study were : Is there any relevant between learning material for SMK/MAK XI 2013 curriculum published by BUMI AKSARA with syllabus? and What is the English textbook learning material for SMK / MAK XI based on the 2013 curriculum published by BUMI AKSARA fulfill criteria based on Nation and Macalister (2010: 160)? The textbooks used in the 2013 curriculum are rarely matched with the syllabus because the teacher thinks that it is not necessary to do so that learning is more relaxed with the method. In the subject of English at SMK N 10 Padang, especially class XI, the textbooks used are published by "BUMI AKSARA" based on the 2013 curriculum. Therefore, researchers are interested in conducting research on Content Analysis of English Learning Materials for SMK / MAK XI 2013 Curriculum “Published by BUMI AKSARA. To get the data, this research conducted at SMKN 10 Padang. The school is located in Simpang Kantor Camat, Jl. Flamboyan, Lubuk Buaya, Kec. Koto Tangah, Kota Padang, Sumatera Barat. Research instrument is the tool used to gathering the data based on the method use. In this study, the researcher use human instrument as the primer instrument. The data collection techniques in this study document analysis. The data analysis in this research was using (1) organizing and familiarizing, (2) coding and reducing, and (3) interpreting and representing. The findings show English Learning material relevant with the syllabus and English textbooks relevant with the criteria Nation and Macalister (2010: 160).Keywords: Learning Material, Textbook, 2013 Curriculum.